SAT0448 Micro-Vessels Hemodynamics Effects Induced by Iloprost in Systemic Sclerosis Patients Evaluated by Laser Doppler Flowmetry. (9th June 2015) - Rotondo, C.; Nivuori, M.; Chialà, A.; Praino, E.; Coladonato, L.; Covelli, M.; Lapadula, G.; Iannone, F.
Abstract : Background: Iloprost is a milestone in the treatment of Raynaud's Phenomenon (RP). However, it has transient hemodynamic effects due to a very short half-time, thereby a treatment protocol has never been validated and the choice of the interval time between infusions is empirical. Objectives: We aimed at evaluating the short and medium term effects of Iloprost on blood flux, measured by Laser Doppler (LD), in patients with RP associated to Systemic Sclerosis (SSc). Methods: 22 SSc patients with RP and 21 healthy controls (HC) were recruited in this study. The SSc patients were aged 52.6±17ys with disease duration of 8, 5±6ys. All patients underwent Iloprost infusions (50ng at 1.5ng/kg/min) for 3 consecutive days. No change of the baseline therapy was allowed. The LD Flowmetry (Periflux System 5000, Perimed) with 4 LD heating probes was used to measure the fingers' skin blood (FSB) flux of the middle phalanx (from the 2nd to the 5th fingers of the left hand). The LD flowmetry was performed at baseline (T0), after 3 consecutive days of Iloprost treatment (T1), and then at 24h (T2) and 7 days (T3) after the last administration of Iloprost. Two experimental protocols were applied: 1) the heating test assessing the variation of FSB flux in response to local heating stress at 44°C (the ratio between induced-heating flux and pre-heating flux (IHF/PHF) evaluates the axon reflex mediated vasodilatation 1 ); 2) the occlusion test assessing the changes of the FSB flux after a 3 min loading period at 200mmHg applied by means of air bracelets taped on the left forearm to occlude the brachial artery (the ratio between the Peak Flux (PF) and Resting Flux (RF) evaluates the nitric oxide (NO) vessels response 2 ). The results are expressed as average across 4 fingers at each time. The comparisons between the different time points were assessed by repeated measures ANOVA and HC and SSc patients were compared by the t-student test. Results: We observed a significant difference between HC and SSc patients before and after the Iloprost infusion. An impaired axon reflex vasoregulation and nitric oxide responses were found in SSc patients, with lower IHF/PHF (heating test) (p=0, 003) and PF/RF (occlusive test) (p<0, 000). However, we observed a prompt improvement, even though transient, of LD parameters following Iloprost infusions in SSc patients. The occlusive test (p=0.051) highlighted a decreasing trend for the recovery time (TR; the time to reach the value of RF after the pressure relief) with a -28, 3% improvement at T1. As regards the post occlusion hyperemic gain flux (po-GF), a time improving was found with the best variation observed at T1; in particular, the percentage difference with respect to T0 was: 33, 8% at T1, 26% at T2, -4, 3% at T3. No significant differences were found between patients with and without left hand digital ulcers, and different nailfold videocapillaroscopy pattern. Conclusions: The microcirculation hemodynamic changes induced by Iloprost seem to vanish within 24h after the last infusion. Although the Iloprost treatment is effective in SSc digital ulcers management, is yet necessary to define the suitable timing to obtain long-lasting benefit. References: Minson, C.T., et al. J. Appl. Physiol. 91, 1619–1626. Grattagliano V., et al. Microvascular Research 80 (2010) 221–226. Disclosure of Interest: None declared